The effects of lifelong blindness on murine neuroanatomy and gene expression - Abbott, Charles W.; Kozanian, Olga O.; Huffman, Kelly J. (Frontiers in Aging Neuroscience, 2015)
Mammalian neocortical development is regulated by neural patterning mechanisms, with distinct sensory and motor areas arising through the process of arealization. This development occurs alongside developing central or peripheral sensory systems. Specifically, the parcellation of neocortex into specific areas of distinct cytoarchitecture, connectivity and function during development is reliant upon both cortically intrinsic mechanisms, such as gene expression, and extrinsic processes, such as input from the sensory receptors. This developmental program shifts from patterning to maintenance as the animal ages and is believed to be active throughout life, where the brain’s organization is stable yet plastic. In this study, we characterize the long-term effects of early removal of visual input via bilateral enucleation at birth. To understand the long-term effects of early blindness we conducted anatomical and molecular assays 18 months after enucleation, near the end of lifespan in the mouse. Bilateral enucleation early in life leads to long-term, stable size reductions of the thalamic lateral geniculate nucleus (LGN) and the primary visual cortex (V1) alongside a increase in individual whisker barrel size. Neocortical gene expression in the aging brain has not been previously identified; we document cortical expression of multiple regionalization genes. Expression patterns of Ephrin A5, COUP-TFI, and RZRß and patterns of intraneocortical connectivity are altered in the neocortices of aging blind mice. Sensory inputs from different modalities during development likely play a major role in the development of cortical areal and thalamic nuclear boundaries. We suggest that early patterning by prenatal retinal activity combined with persistent gene expression within the thalamus and cortex is sufficient to establish and preserve a small but present LGN and V1 into late adulthood.